2018
DOI: 10.31661/jbpe.v8i4dec.926
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Classification Method using Effective Neural Network and Quantitative Magnetization Transfer Imaging of Brain White Matter in Relapsing Remitting Multiple Sclerosis

Abstract: Background: Quantitative Magnetization Transfer Imaging (QMTI) is often used to quantify the myelin content in multiple sclerosis (MS) lesions and normal appearing brain tissues. Also, automated classifiers such as artificial neural networks (ANNs) can significantly improve the identification and classification processes of MS clinical datasets.Objective: We classified patients with relapsing-remitting multiple sclerosis (RRMS) from healthy subjects using QMTI and T1 longitudinal relaxation time data of brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
(35 reference statements)
0
12
0
1
Order By: Relevance
“…7. This article reviewed more than 70 state- [54] non-local means (NLM) NA Brainweb database concept of 5D NLM is used to achieve higher accuracy with lower distortion Valverde et al 2014 [55] FAST and SPM8 NA OASIS database high accuracy WM lesion filling is achieved using FAST and SPM8 techniques Khotanlou and Afrasiabi 2011 [56] spatially constrained possibilistic fuzzy C means (SCPFCM) [37] 2016 differential evolution 81.68 Yeliz, K. and Şengül, H. [63] 2015 feed-forward back propagation 96.75 Esposito et al [40] 2010 evolutionary-fuzzy 88.71 Barry R. Greene et al [41] 2015 logistic regression model 96.90 Ayelet Akselrod-Ballin et al [44] 2009 decision forest 98.50 Simaa Hamid et al [45] 2016 grey level run length matrix 96.90 Yudong Zhang et al [47] 2016 SWE + KNN 97.94 Youngjin Yoo et al [52] 2016 CNN + Euclidean distance transform 72.90 Chang et al [64] 2018 deep CNN 94 Yijun Zhao et al [65] 2017 SVM 81 Punal M. Arabi et al [23] 2017 machine vision 90 Arman Eshaghi et al [66] 2016 random forest 80 Yu-Dong Zhang et al [53] 2018 CNN-PReLU-Dropout 98.23 Zhou and Shen [48] 2018 biogeography-based optimisation with GLCM 92.75 Washimkar and Chede [24] 2017 KNN 97 Rodrigo Antonio Pessini et al [67] 2018 KNN 95 Siar and Teshnehlab [68] 2019 CNN 96.88 Fooladi et al [38] 2018 ENN-AIC 90 Shui-Hua Wang et al [ of-the-art articles to provide broad knowledge of the concepts of MS, and analysed the techniques used for the segmentation and classification of MS diagnoses using MRI and images collected from different databases. Here, the challenges of the lesion segmentation and the classification problem were described and solutions identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7. This article reviewed more than 70 state- [54] non-local means (NLM) NA Brainweb database concept of 5D NLM is used to achieve higher accuracy with lower distortion Valverde et al 2014 [55] FAST and SPM8 NA OASIS database high accuracy WM lesion filling is achieved using FAST and SPM8 techniques Khotanlou and Afrasiabi 2011 [56] spatially constrained possibilistic fuzzy C means (SCPFCM) [37] 2016 differential evolution 81.68 Yeliz, K. and Şengül, H. [63] 2015 feed-forward back propagation 96.75 Esposito et al [40] 2010 evolutionary-fuzzy 88.71 Barry R. Greene et al [41] 2015 logistic regression model 96.90 Ayelet Akselrod-Ballin et al [44] 2009 decision forest 98.50 Simaa Hamid et al [45] 2016 grey level run length matrix 96.90 Yudong Zhang et al [47] 2016 SWE + KNN 97.94 Youngjin Yoo et al [52] 2016 CNN + Euclidean distance transform 72.90 Chang et al [64] 2018 deep CNN 94 Yijun Zhao et al [65] 2017 SVM 81 Punal M. Arabi et al [23] 2017 machine vision 90 Arman Eshaghi et al [66] 2016 random forest 80 Yu-Dong Zhang et al [53] 2018 CNN-PReLU-Dropout 98.23 Zhou and Shen [48] 2018 biogeography-based optimisation with GLCM 92.75 Washimkar and Chede [24] 2017 KNN 97 Rodrigo Antonio Pessini et al [67] 2018 KNN 95 Siar and Teshnehlab [68] 2019 CNN 96.88 Fooladi et al [38] 2018 ENN-AIC 90 Shui-Hua Wang et al [ of-the-art articles to provide broad knowledge of the concepts of MS, and analysed the techniques used for the segmentation and classification of MS diagnoses using MRI and images collected from different databases. Here, the challenges of the lesion segmentation and the classification problem were described and solutions identified.…”
Section: Discussionmentioning
confidence: 99%
“…The values of FPR, NPV, and FDR were observed to be 0.125, 0.933, and 0.133, individually, as indicated by the proposed ENN-AIC model. It was shown that ENN-AIC as an ENN improved the condition of categorisation outcomes compared with RBF and MLP [38].…”
Section: Classification On Different Classifiersmentioning
confidence: 99%
“…The majority of studies were European (k=41/86, Supplementary (k=7) 37,57,58,66,84,90,102 and international (k=8) studies (or >3 test centres). 33,34,55,96,108,110,111,114 The top three study locations were London (k=8), 49,[51][52][53][54]64,73,106 Milan (k=8), 46,48,65,78,92,93,97,99 and Lausanne (k=6).…”
Section: Nationalitymentioning
confidence: 99%
“…The radiofrequency pulse shape was generally Gaussian (k=28), 40,45,61,94,95,98 Sinc-Gaussian (k=5), 35,59,74,82 Fermi (k=4), 57,58,84,90 1-2-1 binomial (k=2), 80,91 and hyperbolic secant pulses (k=1) 71 were also used. Forty studies did not specify pulse shape.…”
Section: Shape Of Mt Pulsementioning
confidence: 99%
See 1 more Smart Citation